2003
DOI: 10.5194/angeo-21-1531-2003
|View full text |Cite
|
Sign up to set email alerts
|

Transient production of F-region irregularities associated with TCV passage

Abstract: Abstract. Transient production of F-region plasma irregularities due to traveling convection vortices (TCVs) was investigated using the Super Dual Auroral Radar Network (SuperDARN) combined with ground magnetometer networks and the POLAR ultraviolet imager. We selected two largeamplitude (100-200 nT) TCV events that occurred on 22 May 1996 and 24 July 1996. It is found that the TCVassociated HF backscatter arises in blobs with spatial scale of a few hundreds km. They traveled following tailward bulk motion of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 39 publications
(44 reference statements)
1
11
0
Order By: Relevance
“…In the interval of 6.0–7.0 min, the negative potential peak moves from 1200 LT to 1100 LT at the latitude of ∼75°, giving an averaged propagation speed of ∼7 km/s. The propagation speeds of the simulated TCVs are comparable with magnetometer observations [ Murr et al , 2002; Kataoka et al , 2001, 2002, 2003a; Amm et al , 2002]. The skew of the simulated TCVs as moving away from noon is also consistent with magnetometer observations [e.g., Friis‐Christensen et al , 1988; Lühr and Blawert , 1994; Moretto et al , 1997; Murr et al , 2002].…”
Section: Ionospheric Disturbancessupporting
confidence: 81%
“…In the interval of 6.0–7.0 min, the negative potential peak moves from 1200 LT to 1100 LT at the latitude of ∼75°, giving an averaged propagation speed of ∼7 km/s. The propagation speeds of the simulated TCVs are comparable with magnetometer observations [ Murr et al , 2002; Kataoka et al , 2001, 2002, 2003a; Amm et al , 2002]. The skew of the simulated TCVs as moving away from noon is also consistent with magnetometer observations [e.g., Friis‐Christensen et al , 1988; Lühr and Blawert , 1994; Moretto et al , 1997; Murr et al , 2002].…”
Section: Ionospheric Disturbancessupporting
confidence: 81%
“…Consequently, the results in this paper are remarkably consistent with previous results in the literature. Our list consists of 825 MIEs over the 8 years and includes “typical” MIEs analyzed in past papers such as 24 January 1996 [ Clauer and Petrov , 2002], 22 May 1996 [ Kataoka et al , 2002, 2003], 24 July 1996 [ Sitar et al , 1998; Sibeck et al , 1999; Kataoka et al , 2003], 6 June 1997 [ Kataoka et al , 2001], and 27 May1998 [ Kataoka et al , 2002]. Also, 8 of 32 events analyzed by Murr and Hughes [2003] are included in our list.…”
Section: Methods Of Analysismentioning
confidence: 99%
“…Smaller‐scale magnetic disturbances sometimes occur on the dayside high‐latitude magnetosphere, and they are often called magnetic impulse event [ Lanzerotti et al , ; Sibeck and Korotova , ], which are associated with smaller‐scale ionospheric convection vortices (traveling convection vortices, or TCVs) and FACs systems [ Friis‐Christensen et al , ; Glassmeier et al , ]. These smaller‐scale features are suggested to arise from localized solar wind dynamic pressure enhancement or dynamic processes in the foreshock region [e.g., Moretto et al , ; Zesta et al , ; Zesta , ; Murr et al , ; Sibeck et al , ; Murr and Hughes , ; Kataoka et al , ]. Kataoka et al [] simulated the FACs systems associated with TCVs by introducing a localized density perturbation and found that the FACs produced have the same polarities as those induced by large‐scale solar wind dynamic pressure enhancement but with much smaller‐scale sizes.…”
Section: Introductionmentioning
confidence: 99%
“…These smaller‐scale features are suggested to arise from localized solar wind dynamic pressure enhancement or dynamic processes in the foreshock region [e.g., Moretto et al , ; Zesta et al , ; Zesta , ; Murr et al , ; Sibeck et al , ; Murr and Hughes , ; Kataoka et al , ]. Kataoka et al [] simulated the FACs systems associated with TCVs by introducing a localized density perturbation and found that the FACs produced have the same polarities as those induced by large‐scale solar wind dynamic pressure enhancement but with much smaller‐scale sizes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation